Dampak Kepuasan Kerja Terhadap Kinerja Guru: Analisis Faktor-Faktor Pendukung dalam Manajemen Pendidikan - Siti Fatmawati (Epistemic: Jurnal Ilmiah Pendidikan, 2023)
This study aims to analyze the impact of job satisfaction on teacher performance at SMP Islam Bakti Asih, which is a crucial factor in improving educational quality. This research employs a qualitative approach with a case study design. The sample consists of 20 teachers selected from a population of 45 teachers using a systematic nonprobability sampling technique. Data were collected through questionnaires, interviews, and document analysis, and the validity and reliability of the instruments were tested to ensure measurement accuracy. The main findings show a significant positive correlation between job satisfaction and teacher performance. Further analysis reveals that school leadership, organizational culture, and supervisory mechanisms also contribute to teacher performance, although job satisfaction remains the dominant factor. This study makes an important contribution to the educational management literature by providing insights into how various factors influence teacher performance. Limitations of this study include the limited sample size and short research duration. The implications of this study include recommendations for improving school policies that focus on enhancing job satisfaction as well as other factors to overall improve teacher performance. Further research is suggested to expand the sample size and extend the research duration to obtain more comprehensive results.